Analisis Konsep Kimia Terkait dengan Pembuatan Surfaktan dari Ampas Tebu - Ai Fiyani; Nanda Saridewi; Siti Suryaningsih (LPPM Universitas Negeri Jakarta, 2020)
Understanding concepts is not enough just to provide information from the teacher, but students must be able to construct their knowledge and understanding of the knowledge they have and apply it to everyday life, including colloidal material. This research was conducted to analyze the chemical concepts associated with making surfactants from sugarcane bagasse. The research method is qualitative descriptive research on 6 Chemistry Education Lecturers at the Tarbiyah and Teacher Training UIN Syarif Hidayatullah Jakarta. The method used is random sampling. The instrument used in the form of rubrics that contain chemical concepts related to the manufacture of surfactants from bagasse with grading scale of 1-3. The implementation consists of: (1) Preparation stage, namely the creation of context content analysis instruments relating to surfactants, and research permits; (2) Research stage, covering all activities at the research site, namely research instrument testing and data collection; (3) Stage of completion, including data processing. The results of the analysis are then calculated the Content Validity Ratio (CVR) and Content Validity Index (CVI). CVI value of 0.72 was obtained, which means that the content is highly related in the production of surfactants from sugarcane bagasse. The results of the analysis of chemical concepts related to the manufacture of surfactants from bagasse, in general have been contained in curriculum books, literature, journals, articles. This shows that the concept in making surfactants can be used in chemistry learning in high school students. The implications of this study make it easier for students to know the chemicals involved in making surfactants. Keywords Chemical concepts, surfactants, bagasse, colloids